Visualizing atomic structure and magnetism of 2D magnetic insulators via tunneling through graphene - Zhizhan Qiu (Nature Portfolio, 2021)
In this work Qiu et al. demonstrate that the application of van der Waals technology to STM/STS will dramatically expand the capabilities of the latter, allowing STM/STS to investigate the structure, electronic properties and magnetism of 2D magnetic insulators at the atomic scale.